2014
DOI: 10.1186/s12989-014-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Is the toxic potential of nanosilver dependent on its size?

Abstract: BackgroundNanosilver is one of the most commonly used engineered nanomaterials (ENMs). In our study we focused on assessing the size-dependence of the toxicity of nanosilver (Ag ENMs), utilising materials of three sizes (50, 80 and 200 nm) synthesized by the same method, with the same chemical composition, charge and coating.MethodsUptake and localisation (by Transmission Electron Microscopy), cell proliferation (Relative growth activity) and cytotoxic effects (Plating efficiency), inflammatory response (induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 66 publications
5
65
0
Order By: Relevance
“…It was reported that expression of concentrations of nanomaterials in mass units is not representative. Number or surface area of nanoparticles (per cm 2 ) seem more precise units with which to compare the toxicity of different nanomaterials [33]. The 1.3 mg/cm 2 dose of AgNPs is equal to AgNP 161 cm 2 /cm 2 of effective surface area (Calculated based on Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that expression of concentrations of nanomaterials in mass units is not representative. Number or surface area of nanoparticles (per cm 2 ) seem more precise units with which to compare the toxicity of different nanomaterials [33]. The 1.3 mg/cm 2 dose of AgNPs is equal to AgNP 161 cm 2 /cm 2 of effective surface area (Calculated based on Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, through the melt processing procedure at the concentration level used, the samples are non-cytotoxic and are suitable for medical uses, although in the literature in some cases a toxic effect of silver NPs was demonstrated. Strong cytotoxic and genotoxic effects of pure silver NPs were found depending on their size, 59 and it was established that small silver NPs (10 nm) are cytotoxic to human lung cells and that the toxicity observed is associated with the rate of intracellular silver release, a 'Trojan horse' effect. 60 However Hackenberg et al 61 found that the cyto-and genotoxic potentials of silver NPs appear at significantly higher concentrations compared with the antimicrobial effective levels at which they are employed in present study, in which a good balance was maintained between antibacterial activity and cytocompatibility as the presented results demonstrate and also in accordance with other researches.…”
Section: Hydrophilicity/biocompatibilitymentioning
confidence: 99%
“…Mutations are assessed at a specific locus -often the HPRT (hypoxanthine phosphoribosyltransferase) or TK (thymidine kinase) genes (Wang et al, 2007;Huk et al, 2014Huk et al, , 2015Gabelova et al, 2017). These assays can detect a range of mutations, including deletions; however, the mouse lymphoma assay (based on the TK gene) detects deletions with higher efficiency compared with the HPRT gene mutation test (Johnson, 2012).…”
Section: Gene Mutationsmentioning
confidence: 99%
“…These assays can detect a range of mutations, including deletions; however, the mouse lymphoma assay (based on the TK gene) detects deletions with higher efficiency compared with the HPRT gene mutation test (Johnson, 2012). HPRT is a purine salvage enzyme, which phosphorylates 'waste' purines and adds them to the cellular DNA precursor nucleotide pool Huk et al, 2014). The HPRT gene is X-linked, with only one active copy per cell, so that a mutation in only one allele is needed for phenotypic expression.…”
Section: Gene Mutationsmentioning
confidence: 99%